Tempos de resistência democrática: os tambores de Bertolt Brecht ecoando na cena teatral brasileira sob o olhar de Fernando Peixoto - Costa, Rodrigo de Freitas (2006)
The purpose of this study is to analyze the construction of the dramatic text Drums in the Night (Bertolt Brecht), directed by Fernando Peixoto, and its staging in Brazil of 1972. Thus, this study aims to valorize the aesthetic and political discussions of Germany after the First World War when Brecht writes Drums -, at the same time that verifies the construction of the character and the plot of the play. And about the recovering of the theoretical proposals of the playwright Bertolt Brecht by the Brazilian director Fernando Peixoto, this study aims to understand the historicity of Peixoto´s discourse when he deals with the transformation of the Brazilian theater along the construction of the 1972 show aiming the verifying of the possible dialogues between the purpose of Peixoto and his group and the society of that time.